Asean GeoSocieEcoPolitics dashboard / Mohammad Zarul Syahir Norsiman, Muhammgad Zameer Dad Ab Rahim and Dr Abdul Rauf Abdul Rasam - Norsiman, Mohammad Zarul Syahir; Ab Rahim, Muhammgad Zameer Dad; Abdul Rasam, Abdul Rauf (College of Built Environment, 2023)
Our project, " Asean GeoSocieEcoPolitics Dashboard system (2021)" utilizes ArcGIS Online to create a dashboard system showcasing the density, political stability, urban population, GDP per capita, and economic growth of Southeast Asian countries by year 2021.